A Classification System to Guide Treatment Needs for Juveniles Who Have Engaged in Abusive Sexual Behavior - Beltrani, Amanda (Criminal justice and behavior, 2023)
Developing an empirically derived classification system that accounts for the heterogeneity of youth could benefit the court, probation officers, and clinicians in making informed management and treatment decisions. This study used a latent class analysis to examine histories and treatment needs patterns among 561 youths who engaged in problematic sexual behavior (PSB) from five U.S. states. Three classes emerged and included: (a) low treatment need (LTN) youth without dysfunctional histories, (b) high transgressions and treatment needs (HTTN) youth with histories of conduct problems, and (c) abuse reactive (AR) youth with histories of maltreatment. Over one year, the LTN group had the lowest levels of treatment needs, the HTTN group had the highest, and the AR group had lower sexual and socioecological but higher general behavior treatment needs. Findings from this study can assist in allocating resources and help guide the individualization of interventions for youth with PSB.